VARIATIONS AND EXPRESSION OF VERY LOW-DENSITY LIPOPROTEIN RECEPTOR (VLDLR) mRNA IN THE LIVER AND OVARY OF A LOW EGG PRODUCTION STRAIN OF LOCAL IRAQI HENS - D. H. Al-Hassani; W. M. Razuki; H. S. Abdulwahid (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This work was conducted to study the association of variations in the VLDLR gene and mRNA expression in the liver and the ovary of local Iraqi hens with some productive and blood traits. The VLDLR gene variations were studied using blood samples of 173 pedigreed hens, 47 weeks old while the expression was studied using tissue samples of the ovary and liver in 30 pedigreed hens, 60 weeks old. Genotypic and allelic frequencies, production traits, and biochemical serum blood were investigated. The results showed that the genotypic and allelic frequencies of the VLDLR in 173 chickens did not agree with Hardy-Weinberg equilibrium (P<0.0307). The genotypic frequencies were 94.7 and 5.3% for both GG and GT genotypes respectively, while the allele frequency of genes G and T were 97.4 and 2.6%, respectively. The results showed an increase (P<0.0001) in egg production and egg weight for the groups of birds that follow the GG genotypes compared to those that follow the genotypes GT. High levels of VLDLR mRNA were present in the liver and the ovary of high-egg-yield layers but were absent or rare in hens with low-egg production rates. The high expression of VLDLR mRNA caused a reduction in serum triglyceride; LDL and VLDL compared with a low expression where showed increases in these traits while other traits were not affected between different levels of expression. This study suggests that the expression level of VLDLR may be a new molecular marker to screen for high egg production in low-egg production local chickens.